Corneal Densitometry as a Predictive Diagnostic Tool for Visual Acuity Results After Descemet Membrane Endothelial Keratoplasty - Schaub, Friederike; Gerber, Fanny; Adler, Werner; Enders, Philip; Schrittenlocher, Silvia; Heindl, Ludwig M.; Cursiefen, Claus; Bachmann, Bjoern O. (American Journal of Ophthalmology, 2019)
PURPOSE: We sought to investigate correlations between preoperative corneal backscatter with visual acuity results after Descemet membrane endothelial keratoplasty (DMEK) in eyes with corneal endothelial disorders.
CRIS-Team WoS Importer:2019-02-21